An Indirect Utility Model of Multiple Car Ownership and Use - Jan Rouwendal; John Pommer (Tinbergen Institute, 2004)
The number of households with two or more cars is steadily increasing over time. The reason is that ownership of a single car imposes restrictions on car use when there are multiple license holders in a household. If such restrictions are severe, the benefits of multiple-car ownership may exceed the additional costs involved. In this paper, we develop a model that is based on the idea that limited substitutability between car use of different drivers is the driving force behind multiple-car ownership. We formulate a model structure in which households can own and use multiple cars. This approach is used to generalize an existing model for ownership and use of a single car two multiple car ownership and use. The extended model is estimated on Dutch data concerning households with one or two cars. An application to the effects of shifting the burden of car taxes from fixed to variable costs is provided.
Keywords: R41; D13; 330; automobile demand; multiple car ownership; demand for car kilometers; Kraftfahrzeug; Verkehrsmittelwahl; Theorie